Bilan de quarante ans de recherches ethnobotaniques en Nouvelle-Guinée, dans la vallée du fleuve Sepik - Christian Coiffier (Revue d'ethnoécologie)
My research on the « traditional » architecture of the Sepik River villages in Papua New Guinea have led me to take an interest in the plant materials used for constructions. This interest allowed me to understand that there existed, and still exists, in this region closely interdependent relationships between the villagers and the plants that surround them. I will briefly retrace my career and the encouragement I received, mainly from André-Georges Haudricourt, Jacques Barrau, Georges Condominas, and Serge Bahuchet. After spending a decade working on the conservation of ethnographic objects, I am bitterly aware of the insufficient recognition of the importance of ethnobotany for a better understanding of these objects, within some major museum institutions.